Calcium Phosphates and Angiogenesis: Implications and Advances for Bone Regeneration. Issue 12 (December 2016) - Malhotra, Angad; Habibovic, Pamela
Abstract : Calcium phosphates (CaPs) are among the most utilized synthetic biomaterials for bone regeneration, largely owing to their established osteoconductive and osteoinductive properties. While angiogenesis is a crucial prerequisite to bone formation, research and applications for CaPs have not appreciated its crucial role. This review discusses how CaPs influence angiogenesis, and highlights promising strategies that address this topic. The objective is to draw attention to the gap in the literature and to highlight the importance of angiogenesis in CaP research, development, and use. Trends: There is increasing demand for synthetic alternatives to a patient's own material in regenerative strategies for damaged or diseased tissues and organs. In bone regeneration, CaPs are promising candidates. While traditional CaP designs were focused on the initiation and guidance of new bone formation, the next generation of CaP materials needs to better address the complexity of the bone-healing environment. Successful CaP bone-graft substitutes for clinically relevant bone defects must be able to establish and maintain proper vasculature. Instead of adding cells or growth factors to establish both angiogenesis and bone growth, the focus is now on inorganic or small molecules, and on the improved design of CaPs. These priorities aim to enhance the clinical performance and affordability of CaPs.